2011
DOI: 10.2337/db11-0259
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Deletion of SOCS1 Increases Sensitivity to LPS and Palmitic Acid and Results in Systemic Inflammation and Hepatic Insulin Resistance

Abstract: OBJECTIVEMacrophage secretion of proinflammatory cytokines contributes to the pathogenesis of obesity-related insulin resistance. An important regulator of inflammation is the suppressor of cytokine signaling-1 (SOCS1), which inhibits the JAK-STAT and toll-like receptor-4 (TLR4) pathways. Despite the reported role of SOCS1 in inhibiting insulin signaling, it is surprising that a SOCS1 polymorphism that increases SOCS1 promoter activity is associated with enhanced insulin sensitivity despite obesity. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 50 publications
1
55
0
4
Order By: Relevance
“…We have further shown that SOCS1 also inhibits expression of MyD88 and prevents TLR-and IL-1 receptor-mediated NF-κB activation (13). Consistent with these observations, SOCS1-knockout mice show increased production of proinflammatory cytokines, such as TNF-α, IL-12, and IFN-γ, in response to TLR ligands in vitro (14,15) and in vivo (16,17). The precise role of SOCS1 in bacterial sepsis, however, remains undetermined.…”
Section: Introductionsupporting
confidence: 68%
“…We have further shown that SOCS1 also inhibits expression of MyD88 and prevents TLR-and IL-1 receptor-mediated NF-κB activation (13). Consistent with these observations, SOCS1-knockout mice show increased production of proinflammatory cytokines, such as TNF-α, IL-12, and IFN-γ, in response to TLR ligands in vitro (14,15) and in vivo (16,17). The precise role of SOCS1 in bacterial sepsis, however, remains undetermined.…”
Section: Introductionsupporting
confidence: 68%
“…In contrast, we show that β1 -/-BMT mice develop greater HFD-induced hepatic insulin resistance than WT BMT controls. Since adipose tissue cell size appears to be the primary factor dictating macrophage recruitment and adipose tissue inflammation (55,56) and mice lacking whole-body AMPK β1 do not develop obesity, this may be a likely explanation for the disparity between mice with hematopoietic compared with global deletion of β1.…”
Section: Discussionmentioning
confidence: 99%
“…WT and β1 -/-bone marrow was isolated from the femur and tibia of 10- to 12-week-old mice as described previously (56). For palmitate treatments, day-8 BMDMs were serum starved 3-4 hours before incubation with the indicated palmitate concentrations at the indicated times, conjugated to 2% (w/v) fatty acid-free and low endotoxin BSA (SigmaAldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We turned to the well-studied K/BxN serum-transfer system, which mimics many of the clinical and immunological features of human inflammatory arthritis (22). The impact of denervation on the response to arthritogenic serum by mice was astonishingly parallel to the effect of central or peripheral denervation on subsequent RA development by humans.…”
Section: Discussionmentioning
confidence: 99%